2017
DOI: 10.1111/his.13201
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous mesenchymoma of bone: a single‐institution experience with molecular investigations and a review of the literature

Abstract: This very rare bone tumour has a typical radiological and histological pattern and a favourable survival outcome after treatment. Local recurrences can be prevented with complete surgery. Fibrocartilaginous mesenchymoma does not seem to be related genetically to fibrous dysplasia, low-grade osteosarcoma and de-differentiated chondrosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Rare cases of FCD demonstrate enchondral ossification as in FM; however, FCD principally consists of bland spindle cells and characteristic, irregular, curvilinear trabeculae of woven bone, lacking osteoblastic rimming. Furthermore, GNAS mutations are detected in many cases of FCD, whereas no specific molecular aberrations have been found in FM [2]. Although the GNAS mutation was not tested in the present case, differentiation from FCD was not difficult due to the tumor's overall histological characteristics.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Rare cases of FCD demonstrate enchondral ossification as in FM; however, FCD principally consists of bland spindle cells and characteristic, irregular, curvilinear trabeculae of woven bone, lacking osteoblastic rimming. Furthermore, GNAS mutations are detected in many cases of FCD, whereas no specific molecular aberrations have been found in FM [2]. Although the GNAS mutation was not tested in the present case, differentiation from FCD was not difficult due to the tumor's overall histological characteristics.…”
Section: Discussionmentioning
confidence: 72%
“…Since then, there have been debates in the literature regarding FM as a separate neoplasm or one that coincides with FCD [5][6][7]. However, several studies, particular-ly molecular analyses, have demonstrated that FM is not genetically related to FCD, which has a characteristic GNAS (guanine nucleotide-binding protein α-stimulating polypeptide) mutation [2]. Accordingly, the 5th edition of the World Health Organization classification of bone tumors newly listed FM as an independent tumor entity [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologically, it is composed of mildly atypical spindle cells admixed with nodules of hyaline cartilage that have a ‘growth plate‐like’ appearance and undergo endochondral ossification. In a recent small series, GNAS and IDH1 / 2 mutations were absent, as was MDM2 amplification, providing molecular support for fibrocartilaginous mesenchymoma being distinct from several other entities that show overlapping morphology (fibrocartilaginous dysplasia, chondrosarcoma, and low‐grade osteosarcoma, respectively) 100 …”
Section: Bonementioning
confidence: 89%